Self-determination struggles in pursuit of the democratic confederalist ideal - Miley, Thomas Jeffrey (Black Rose Books, 2023)
"This volume examines the theory and meaning of self-determination today through an exploration of the work of figures such as Rosa Luxembourg, Frantz Fanon, and Abdullah Öcalan, the leader of the Kurdish Freedom Movement. Leaving no stone unturned, Self-Determination Struggles not only includes radical political movements and thinkers, but makes them the core of its investigations, presenting them in granular, revealing detail rare to find elsewhere."
Keywords: Autonomiebewegung; Demokratie; Völkerrecht; Aktivist; Selbstbestimmungsrecht; Revolutionaries; Political activists; Radicalism; Self-determination, National; Democracy